Access to the population, financing and availability times of antineoplastic drugs incorporated into the SUS between 2012 and 2024 - Salustio Pires, Bernardo; Bratke, João; do Nascimento Santos Costa, Julia; de Souza Nars, Mariana; Mussolino, Maria Fernanda (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: The study aimed to evaluate the effectiveness of the process of incorporating antineoplastic drugs into the Sistema Único de Saúde (SUS) from 2012 to October 2024. Whether these treatments are being made available in a timely manner and what limitations exist was investigated. Methods: A retrospective analysis of CONITEC reports was used, where data on 24 drugs was collected, including dates of incorporation and publication in the Diário Oficial da União, as well as information on published oncology therapeutic guidelines, antineoplasic drug costs and transfer values for Autorizações de Procedimentos Ambulatoriais (APAC). Results: The results showed that, from a total of 24 antineoplasic drugs incorporated during the analyzed period, a significant amount experience limitations on access, including 7 drugs not included on therapeutic guide lines and 15 with insufficient federal transfer values. In total, treatment costs for 15 technologies are over 100% above values determined for APAC. Conclusions: The study revealed that important barriers compromise availability of incorporated antineoplasic drugs in SUS, with treatment costs currently significantly outweighting APAC values. There exists a visible need for efficient alternatives for finance and management in onco logy, as demonstrated by the examples of blinatumomab and drugs centrally acquired by the Ministry of Health, to improve access to oncology in the SUS.